30. TESTICULAR TORSION: EXPERIENCE IN DIAGNOSING AND TREATMENT OF PATIENTS AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Describe clinical, paraclinical characteristics, and surgical results of patients with testicular torsion; identify some factors associated with the ability to preserve the testicles in this group of patients. Methods: A cross-sectional study. Research results: In the study, a total of 75 patients who underwent testicular torsion surgery were included. The mean age of the patients was 16.55 ± 8.12 years old, with the majority falling into two age groups: 0-15 years old (56%) and 16-25 years old (37.3%). Testicular torsion cases were more common in cold weather, such as winter. All patients experienced symptoms of scrotal pain and high hanging testicles, with additional signs like vomiting/nausea present in 25.33% of cases. The percentage of orchiectomy (removal of the testicle) was 78.9%. After undergoing orchiectomy, 40.7% of patients experienced psychological disorders to varying degrees. More than 1 turn testicular torsion, late arrival time and purple-black testicular color are risk factors for orchiectomy. Conclusion: Testicular torsion is an emergency in the field of andrology. Understanding the age group distribution and time of disease onset helps early diagnosis and appropriate treatment, increasing the rate of testicular preservation. Psychological disorders after orchiectomy need to receive attention from both doctors and the patient’s family.
Keywords: Testicular torsion, Orchiectomy, Testicular preservation, Testicular Doppler ultrasound.